ENHANCED PHYSICO-MECHANICAL AND THERMAL PROPERTIES OF WASTE HDPE/LDPE BLENDS REINFORCED WITH Borassus aethiopum FIBRES - Shinggu, Yamta Danbaki; Jacob, Joseph (FUDMA JOURNAL OF SCIENCES, 2025)
This study evaluated the effects of Borassus aethiopum fibre (BAP) on waste HDPE-LDPE blends. The (Borassus aethiopum fibre (BAP) on waste HDPE-LDPE) materials were compounded on a Two Roll Mill and compression moulding machines. Properties such as density, water absorption, tensile strength, elastic modulus, flexural strength and hardness values were evaluated using standard procedures. The materials were further subjected to dynamic mechanical properties test in order to evaluate the influence of BAP fibre incorporation on the storage modulus, loss modulus and damping parameter of waste HDPE-LDPE blends. Optimal mechanical properties (tensile strength = 77.5 MPa, stiffness = 3.5 GPa) were achieved at 40 wt% BAP loading. This composition has corresponding minimal water absorption of 0.45 % after 240-hrs immersion period at room temperature. Similarly, dynamic mechanical properties results indicated that the storage modulus and load bearing capability of were found to be maximum (1.2 GPa) for a composite with 40 % weight of BAP fibre compared (to 400 MPa of the unreinforced) while a decrease in loss modulus was observed with increase in temperature and frequency. This indicates that incorporation of BAP fibre into waste HDPE-LDPE blends improved its physical, mechanical and dynamic mechanical properties with these properties increasing with the weight percentage of BAP incorporated up to 40 % and a sudden decrease at 50 % weight of BAP.